2014
DOI: 10.1371/journal.pgen.1004331
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid-Related Orphan Receptor γ (RORγ): A Novel Participant in the Diurnal Regulation of Hepatic Gluconeogenesis and Insulin Sensitivity

Abstract: The hepatic circadian clock plays a key role in the daily regulation of glucose metabolism, but the precise molecular mechanisms that coordinate these two biological processes are not fully understood. In this study, we identify a novel connection between the regulation of RORγ by the clock machinery and the diurnal regulation of glucose metabolic networks. We demonstrate that particularly at daytime, mice deficient in RORγ exhibit improved insulin sensitivity and glucose tolerance due to reduced hepatic gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
83
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 38 publications
5
83
0
Order By: Relevance
“…Within the NR1F subfamily of NRs, RORgt has garnered much attention due to its role in T H 17 cells. However, its contribution to obesity and insulin resistance has been recently demonstrated (Meissburger et al, 2011;Takeda et al, 2014). The discovery that the potent LXR agonist T0901317 [N-(2,2,2-trifluoroethyl)-N-[4-[2,2,2-trifluoro-1-hydroxy-1-(trifluoromethyl)ethyl]phenyl]-benzenesulfonamide] also functioned as an inverse agonist for RORa and RORg and SR1555 .…”
Section: Discussionmentioning
confidence: 99%
“…Within the NR1F subfamily of NRs, RORgt has garnered much attention due to its role in T H 17 cells. However, its contribution to obesity and insulin resistance has been recently demonstrated (Meissburger et al, 2011;Takeda et al, 2014). The discovery that the potent LXR agonist T0901317 [N-(2,2,2-trifluoroethyl)-N-[4-[2,2,2-trifluoro-1-hydroxy-1-(trifluoromethyl)ethyl]phenyl]-benzenesulfonamide] also functioned as an inverse agonist for RORa and RORg and SR1555 .…”
Section: Discussionmentioning
confidence: 99%
“…The retinoic acid receptor-related orphan receptors, RORα-γ (NR1F1-3), are members of the nuclear receptor superfamily and function as ligand-dependent transcription factors that are involved in the regulation of a wide range of physiological processes, including immune response, lipid/glucose homeostasis, and circadian rhythm (Jetten, 2009; Jetten et al, 2013; Takeda et al, 2014a,b). They are considered to be orphan receptors because their endogenous ligands have not yet been agreed upon definitively, and they have been identified with distinct tissue distributions and biological activities (Jetten, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Only RORα and RORγ are highly expressed in the liver, while RORβ is expressed mainly in the central nervous system (Forman et al 1994;Andre et al 1998;Takeda et al 2012). Studies of total body knockout mice reported that both RORα-and RORγ-deficient mice exhibited improved insulin sensitivity and glucose tolerance with decreased hepatic gluconeogenesis (Takeda et al 2014a;Kadiri et al 2015). RORα-deficient mice, which suffer from severe cerebellar defects and display a staggerer phenotype (Sidman et al 1962;Dussault et al 1998;Steinmayr et al 1998), also exhibited lower total body fat and were resistant to age-induced white adipose tissue (WAT) and brown adipose tissue (BAT) hypertrophy (Kang et al 2011).…”
mentioning
confidence: 99%